The paradox of corporate sustainability: analyzing the moral landscape of Canadian grocers - Taylor, Samantha; Charlebois, Sylvain; Crowell, Tammy; Cross, Bryce (Frontiers in Nutrition, 2024)
Food prices have experienced unprecedented increases in recent times. Simultaneously, grocers are facing allegations of capitalizing on inflation to generate unjustifiable profits. Escalating expenses and a lack of transparency have engendered heightened consumer skepticism. This perceived presence of barriers and excessive profitability gives rise to ethical concerns. Our study delves into the ethical landscape surrounding Canadian grocers, aiming to probe the public's demand for accountability. To comprehend the factors responsible for the transformation in consumer perception of Canadian grocers in 2022, we conducted an analysis utilizing data from consumers, corporate watchdogs, and industry sources. We extended Hahn et al.'s (2018) paradox perspective corporate sustainability framework to include a historical aspect to use as our analytical lens. This study sheds light on the alterations in circumstances that have led Canadian consumers to question entire industries and accounting practices that were previously considered unproblematic. As a remedy, we recommend the establishment of a voluntary code of conduct for grocers and an enhancement in the transparency of financial reporting. Paradoxically, corporate profits may continue to grow when societal needs are no longer perceived as being neglected or, even worse, exploited.